TDCS, OFDM, and MC-CDMA a brief tutorial. - Chakravarthy, Vasu.
This article gives a brief tutorial on transform-domain communication system (TDCS), OFDM, and MC-CDMA. The primary goal of this article is to give a detailed description of the TDCS transmitter and receiver systems and to highlight the fundamental differences relative to OFDM and MC-CDMA. The fundamental idea in TDCS is to synthesize a smart adaptive waveform to avoid interference at the transmitter instead of the more traditional mitigating of interference at the receiver. Unlike OFDM and MC-CDMA, TDCS has very little exposure in the current literature.
Keywords: MC-CDMA.; OFDM; interference; receiver systems; smart adaptive waveform; transform-domain communication system; transmitter systems